EFFECTIVENESS OF AN INTEGRATED PHYSICAL THERAPY PROGRAM FOR MATURE WOMEN WITH ISCHEMIC ACUTE STROKE IN THE LONG-TERM REHABILITATION PHASE - Павлова, Тетяна; Федусь, Богдана (SWorldJournal, 2026)
The article presents the results of a study of the effectiveness of an integrated physical therapy program for mature women after ischemic acute cerebrovascular accident at the long-term rehabilitation stage. The feasibility of combining the outpatient st